Composition of Sauvignon blanc Grapes as Affected by Pre-veraison Canopy Manipulation and Ripeness Level - Hunter, J.J.; Volschenk, C.G.; Marais, J.; Fouche, G.W. (South African Journal of Enology and Viticulture, 2017)
The implications of pre-veraison canopy management and ripeness level (19°B and 21°B) on microclimate and grape and must composition were determined on intensively micro-sprinkler irrigated Vitis vinifera L. cv. Sauvignon blanc/110 Richter vines, grown on a vertical trellis in the Breede River Valley of South Africa. Rows were east-west orientated and vines spaced 2.75 m x 1.5 m. Spurs were spaced approximately 15 cm apart. Canopy management consisted of different combinations of seasonal practices (suckering, shoot positioning, topping, leaf thinning) during the pre-veraison growth period (just after budding to pea size berry) in order to accommodate foliage and to improve the canopy microclimate. Treatments that included leaf thinning improved the light conditions in the canopy without a noticeable effect on other microclimate parameters as well as bunch and berry sap temperature. The must pH remained relatively stable, with an increase in ripeness level from 19°B to 21°B, whereas the rest of the measured grape composition components followed a decreasing pattern during this period. Treatments that included leaf thinning tended to increase titratable acidity and decrease pH at both ripeness levels. Additional leaf thinning (up to the lower half of the canopy at pea size) increased the glucose and fructose concentrations without changing their ratio. It also decreased the malic acid concentrations of the berries, whereas the free-amino-nitrogen content of the must was stimulated. Furthermore, leaf thinning in general increased the monoterpene content (fruity aroma) and apparently enhanced the 2-methoxy-3-isobutylpyrazine content (grassy/green pepper aroma), thereby increasing the total measured aroma profile. Both palate and flavour profiles were therefore changed by applying pre-veraison seasonal canopy management. The data emphasised the importance of the correct timing and application of canopy management. This seemed to be of great significance in the realisation of an improved grape composition, even for S. blanc subjected to a relatively hot terroir.